The Association and Pathogenesis of SERPINA3 in Coronary Artery Disease - Li, Bo; Lei, Zhijun; Wu, You; Li, Bingyu; Zhai, Ming; Zhong, Yuan; Ju, Peinan; Kou, Wenxin; Shi, Yefei; Zhang, Xianling; Peng, Wenhui (Frontiers in Cardiovascular Medicine, 2021)
Background: Serine proteinase inhibitor A3 (SERPINA3) has been discovered involving in the pathology of human diseases, but little is known about the role of SERPINA3 in coronary artery disease (CAD). The objective of this present study is to determine its association and pathogenesis in CAD. Methods: 86 patients with CAD and 74 patients with non-CAD were compared. The plasma SERPINA3 levels was measured by ELISA. Logistic regression and receiver-operating characteristic (ROC) analysis were performed to illustrate the association between plasma SERPINA3 levels and presence of CAD. In vitro, real-time PCR (RT-PCR) and immunofluorescence staining was used to determine the expression of SERPINA3 in atherosclerotic plaques and its component cells. Then RASMCs was transfected with siRNA to knockdown the expression of SERPINA3 and HUVECs were treated with SERPINA3 protein. Edu assay and scratch assay were used for assessing capability of proliferation and migration. Cell signaling pathway was assessed by western blot and RT-PCR. Results: Patients with CAD [104.4(54.5-259.2) ug/mL] had higher levels of plasma SERPINA3 than non-CAD [65.3(47.5-137.3) ug/mL] (P =0.004). After fully adjusted, both log-transformed and tertiles of plasma SERPINA3 levels were significantly associated with the presence of CAD. While its diagnostic value is relatively low and the area under ROC curve was 0.64 (95% CI: 0.55-0.73). Secreted SERPINA3 might increase the inflammatory factors expression in HUVECs. Vascular smooth muscle cells had the highest SERPINA3 expression in aorta. The knockdown of SERPINA3 in RASMCs attenuate the capability of proliferation and migration. The phosphorylated IκBα and downstream pathway was inhibited when SERPINA3 is knockdown. Conclusions: Elevated plasma SERPINA3 levels were associated with the presence of CAD. SERPINA3, increasing expression of inflammatory factors in HUVECs, and regulating VSMCs proliferation, migration and releasing of inflammatory factors through NF-κB signaling pathway, played a significant role in the pathogenesis of atherosclerosis.